Product Characteristics, Location and Competitive Advantage: Evidence from Electronic Gadget Outlets - Lawal, Azeez Tunbosun; Jimoh, Abdulrasheed; Brimah, Amudat Bolatito; Lewis-Ambrose, Dana; Ismail, Dare; Bakare, Wasiu Omotayo (Acta Universitatis Danubius. Œconomica, 2024)
The purpose of this study is to examine the relationship between product characteristics (quality and price), location and competitive advantage of electronic gadget outlets within Ilorin metropolis of Kwara State. This study is hinged onResource-based View Theory, with the intentionto identify and leverage the unique resources of electronic gadget outlets to gain a sustainable competitive advantage. A survey research design was employed, employing a purposive sampling technique of 364customers of selected electronic gadget outlets within Ilorin metropolis of Kwara State. Data were collected using the Instrument titled “Product Characteristics, Location and Competitive Advantage Questionnaire (PCLACAQ)”.Both Statistical Packages for Social Sciences (SPSS) and Partial Least Square (PLS-SEM) software were used to analyze the data collected. The results indicated that location correlates with the attainment of organizational competitiveness of gadget outlets. According to the study, quality is a good indicator of competitive advantage of gadgets outlets; this indicates that quality produce competitive advantage to the organization. Results from this study shows that quality and location is a good indication of the performance of electronics stores. This suggests that quality and location results in a competitive advantage for the company, while price does not contributes to enhanced organisational performance. The current research however illustrates that improving an organization's quality and location improve both its performance and its advantage over its competitors. There are some implications in this study for managers in the electronic gadget outlets. Management must ensure the quality assurance of the electronic gadget products is not compromised; this would further boost the corporate image of their business for expected productivity and longevity. Researchers and industry professionals can gain valuable insights into the strategies and factors that drive success in this particular market segment by investigating the relationship between location, product characteristics (price and quality), and competitive advantage of electronic gadget outlets. This study contributes to the existing knowledge base, provides guidance to retailers, and supports decision-making processes in the ever-changing landscape of electronic gadget retail.